(untitled) (Globalization and Business, 2023)
In most countries of the modern world, the problem of overcoming poverty is hanging like a sword of Damocles. The rich and poor exist from the very beginning of the mankind, having the open and hidden opposition towards each other. Namely, this can be named, one of the main reasons of outbreaks of revolutions in different countries, followed by the destruction and victims.Even the modern civilized world has not been able to solve this universal challenge, in spite of all the scientific and technological achievements.For Poverty alleviation all the States need to carry out the right and rational social and economic policy. Simultaneously, it is necessary to find ways to balance the uneven distribution of the World wealth, overcome the cultural barriers, and the most important thing is to undertake more effective measures for inclusive development of economics of the developing and backward countries.